Durability related properties of low calcium fly ash based geopolymer concrete - Olivia, Monita (Curtin University, 2011)
Geopolymer material using by-products can lead to a significant reduction of the carbon footprint and have positive impact on the environment. Geopolymer is recognized as an alternative construction material for the Ordinary Portland Cement (OPC) concrete. The mechanical properties of geopolymer concrete are superior for normal exposure environments. In terms of durability in the seawater, a limited number of publications were available. The seawater environment contains chloride ions and microorganisms that are harmful for reinforced concrete structures. Hence, a study of the durability of fly ash geopolymer concrete is essential when this material is to be used in a real application. The present study aims to investigate the durability of fly ash geopolymer concrete mixture in a seawater environment such as seawater resistance and corrosion of steel reinforcement bars. The development of mixtures and their mechanical properties were also presented.The concrete mixtures were developed using the Taguchi optimization method. Three mixtures, labelled T4, T7, T10 and a control mix were investigated further. Mechanical properties such as compressive strength, tensile strength, flexural strength, Young’s Modulus of Elasticity were determined for each mix. In addition the water absorption/AVPV and drying shrinkage were also measured. The seawater resistance study comprises chloride ion penetration, change in strength, change in mass, change in Young’s Modulus of Elasticity, change in effective porosity and change in length. The corrosion performance of steel reinforcement bars in fly ash geopolymer concrete was determined by measuring the corrosion potential by half-cell potential, accelerated corrosion test by impressed voltage method and microbiologically influenced corrosion incorporating algae. The microstructure of the samples was also investigated using SEM and microscope.It can be summarized that the fly ash geopolymer concrete has an equivalent or higher strength than the OPC concrete. The seawater resistance revealed a high chloride ion penetration into the fly ash geopolymer concrete due to lack of a chloride binding ability and continuous hydration under aqueous medium. The geopolymer concrete had a higher strength and small expansion following exposure to wetting-drying cycles. There was a rapid depassivation of steel reinforcement bars in fly ash geopolymer concrete, although it has a smaller corrosion rate than the OPC concrete. This could delay the pressure in generating cracks in the concrete cover which is not favourable in the long term, due to a sudden loss of load carrying capacity. A novel study on the corrosion performance in algae medium demonstrated a risk of steel bar corrosion in fly ash geopolymer concrete due to the low alkalinity of this concrete. It can be concluded that the low calcium fly ash geopolymer offers some advantages in durability for reinforced concrete in seawater environments.